Beyond the claim of random sampling - Jamil, Nur Izzah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Probability sampling involves selecting individuals so that everyone in the population has a known and equal chance of being chosen, usually through randomization methods such as random number tables or computer-generated sequences to ensure a representative sample. In contrast, non-probability sampling selects participants based on convenience, judgment, or specific criteria, making it easier to conduct but less representative. In research, the term “random” has a strict meaning, although it is sometimes used loosely when the actual method is closer to non-probability sampling. This discussion highlights stratified sampling and quota sampling, which aim to represent important subgroups within a population.